ปฏิกิริยาเอสเทอริฟิเคชันของกลีเซอรอลกับกรดอะซิติก โดยใช้กรดทังสโตฟอสฟอริกตรึงบนวัสดุแบบมีรูพรุนที่เติมหมู่ฟังก์ชันอะมิโน - ชุติมา ตังกุ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Tungstophosphoric acid (HPW) was successfully immobilized on the surface of amino-functionalized SBA-15 and MCM-41, designated as SBA-15-N-H20 and MCM-41-N-H20, respectively. Their characteristics were investigated using XRD, N2 adsorption-desorption, and FT-IR techniques. The characterization results showed that the synthesized materials exhibited highly ordered mesoporous structure, indicating that the structures of SBA-15 and MCM-41 supports were preserved after the modification with aminosilane and HPW. The surface area, pore diameter, and acidity of SBA-15-N-H20 were 337 m² g-¹, 8.06 nm, and 136 μmol g-¹, respectively; while those of MCM-41-N-H20 were 290 m² g-¹, 2.43 nm, and 93 μmol g-¹, respectively. The synthesized materials were tested as heterogeneous catalysts for the esterification of glycerol with acetic acid using a glycerol/acetic acid molar ratio of 1:6, 100 °C, 3 h, and 3 wt.% catalyst loading. The glycerol conversion over SBA-15-N-H20 (82.7%) was higher than that achieved over MCM-41-N-H20 (78.1%) mainly due to its higher acidity. In addition, the results indicated that the pore sizes of the catalysts played an important role for the selectivity of acetin products. Specifically, the use of MCM-41-N-H20 having smaller pore sizes led to a higher selectivity towards monoacetin while that of SBA-15-N-H20 having larger pore sizes gave higher selectivities towards bulkier diacetin and triacetin. Effect of reaction parameters including reactants ratio, reaction temperature, and catalyst loading was also studied. In addition, the study of catalyst reusability showed that MCM-41-N-H20 could be reused up to six cycles without significant loss of catalytic activity due to the strong interaction between the amino groups and the HPW anions.